Productivity of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) in coastal areas of northern Sweden - Zhang, Bo (SLU/Southern Swedish Forest Research Centre, 2012)
Productivity of Norway spruce (Picea abies) and Scots pine (Pinus sylvestris) was studied on 12 sites in coastal areas of northern Sweden. On each site, sample plots were placed in adjacent Norway spruce and Scots pine stands with similar ages in between. Basal area, tree height, Site Index, volume production, simulated maximum mean annual increment (MAImax) and tree vitality were compared for the two species. Average basal area at the time of measurement was 30.4% larger for Scots pine stands than for Norway spruce stands. The difference between the two species in basal area increment during the last 10 years was related to stand age. Basal area increment of Scots pine was larger than Norway spruce for young stands, and smaller than Norway spruce for older ones. Average height was 2.3 m higher for Scots pine stands than for Norway spruce stands. Height growth in the last year was also higher for Scots pine. Site Index (SI) for the two species was similar on most sites except for three sites, where SI for Scots pine was more than 10% larger than for Norway spruce. Total volume production for Scots pine stands was 29.9% higher than for Norway spruce stands. On average, simulated MAImax was 13.8% higher for Scots pine than for Norway spruce, and age for reaching MAImax was 16 years later for Norway spruce than Scots pine. Tree vitality was higher for Norway spruce than for Scots pine largely due to browsing by moose. Total damage rates were 16.0% and 4.6% for Scots pine and Norway spruce, respectively. The results from this study indicate that Scots pine has higher productivity than Norway spruce in coastal areas of northern Sweden. However, as is suggested by the comparison between the current results and those from a previous study in the interior northern Sweden, spruce is more recommendable in coastal areas than in interior locations from both the productivity and economic point of view. Yet, market fluctuation, climate change and/or other social matters should also be considered for selecting regeneration species.